Educational Management Model for Enhancing Medical Professional Competence in Forensic and Medicolegal Education through Artificial Wound Simulation - Nola T S Mallo; Henny Nikolin Tambingon; Orbanus Naharia; Ruth Umbase (JR Education, 2026)
This article examines the management of competency improvement for participants in a medical professional education program in forensic and medicolegal sciences. The central problem is the gap between expected forensic-medical competence and the limited learning conditions experienced during a short clinical rotation, particularly the scarcity of real forensic cases that can be observed and practiced directly by learners. The study used a qualitative case-study approach based on in-depth interviews, observation, and documentation. The analysis was organized through the educational management functions of planning, organizing, actuating, and controlling (POAC), and was integrated with competency-based medical education, simulation-based learning, and continuous quality improvement. The findings show that competency improvement requires careful planning of competency needs, an integrated curriculum, structured resources, active implementation through lectures, case discussions, laboratory practice, artificial wound simulation, and repeated writing exercises for Visum et Repertum. Evaluation through formative feedback, summative assessment, and simulation-based Objective Structured Clinical Examination (OSCE) indicated improvement in descriptive, analytical, documentary, confidence, and collaborative competencies. The article proposes an educational management model that integrates POAC with artificial wound simulation as an innovation to address limited rotation time and real-case scarcity. The model strengthens technical competence, reflective learning, medicolegal reasoning, and quality assurance in forensic medical education.